2017
DOI: 10.3892/ol.2017.7581
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone II is a potent candidate for treatment of lipopolysaccharide-induced acute lung injury in rat model

Abstract: Abstract. The present study aimed to investigate the effect of tanshinone II, isolated from Salvia miltiorrhiza Bunge, on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in rats. Male Sprague-Dawley rats were divided into three groups: Control, LPS and tanshinone II. Animals in the tanshinone II and LPS groups were administered 10 mg/kg LPS, whereas those in the control group received an equal volume of normal saline. Tanshinone II treatment group were injected with 30 nm/kg tanshinone II at 1 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Increasing reports demonstrate that tan IIA possesses therapeutic potential for numerous diseases with few side effects ( 30 , 32 34 , 36 , 38 ). Among the numerous biological activities of tan IIA, greater attention has been focused on increasing the sensitivity of tumor cells to chemotherapeutic drugs ( 45 , 46 ). Our previous studies demonstrate that the combination of tan IIA with ADM functions to inhibit the malignant biological behaviors of NSCLC cells in a synergistic way and was able to enhance the antitumor effect of ADM ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports demonstrate that tan IIA possesses therapeutic potential for numerous diseases with few side effects ( 30 , 32 34 , 36 , 38 ). Among the numerous biological activities of tan IIA, greater attention has been focused on increasing the sensitivity of tumor cells to chemotherapeutic drugs ( 45 , 46 ). Our previous studies demonstrate that the combination of tan IIA with ADM functions to inhibit the malignant biological behaviors of NSCLC cells in a synergistic way and was able to enhance the antitumor effect of ADM ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA is derived from the dried root or rhizome of Salviae miltiorrhizae Bge [ 84 ] and has anti‐inflammatory, [ 85 ] antioxidant [ 86 ] and neuroprotection activities. [ 87 ] Tanshinone IIA decreased the levels of ROS and MDA, increased the activities of SOD and GSH‐Px, reduced the levels of phosphorylate PKR‐like (p‐PERK), phosphorylate eukaryotic initiation factor 2 and binding immunoglobulin heavy chain protein (Bip) in Aβ‐treated HT22 cells.…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
“…Specific pathogen-free (SPF) male Wistar rats (2 months old, 180 ± 200 g) were purchased from Charles River Experimental Animal Co., Ltd. (Beijing, China) and raised in the Xiamen University Laboratory Animal Center (License number: SYXK (Min) 2018-0010). The animals were housed one week before the start of experiment under standard laboratory conditions at a stable temperature (22 ± 2 °C), humidity (50 ± 10%), and a 12/12 h light/dark cycle with food and water ad libitum [ 15 , 16 ]. All animal procedures were carried out at the Xiamen University Laboratory Animal Center and approved by the Ethics Committee of the First Affiliated Hospital of Xiamen University.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that SMI has a protective effect on ALI [14,15], but the mechanism remains unclear.…”
Section: Salvia Miltiorrhiza Injection (Smi) a Chinese Materiamentioning
confidence: 97%
See 1 more Smart Citation